2011
DOI: 10.2298/hel1154067b
|View full text |Cite
|
Sign up to set email alerts
|

Non-parametric stability analysis of sunflower oil yield trials

Abstract: locations in the region of Vojvodina and central Serbia was carried out in order to study GEI (genotype × environment interaction) on oil yield and stability of hybrids using non-parametric measures of stability. The non-parametric test indicated the presence of significant crossover interaction [G(E) and E(G)]. Non-parametric measures S i (1) and S i (2) were used to determine stability of sunflower hybrids. The level of association among stability measures was assessed using Sperman's rank correlation. Signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 11 publications
4
10
0
Order By: Relevance
“…The significant genotype × location interaction implied that the responses of the genotypes changed depending on the environmental conditions. These finding are in agreement with the results reported by Balalić and Zorić (2013). There was no significant genotype × year interaction that means genotype behavior in a location between years is not significant.…”
Section: Analysis Of Variance and Nature Of Ge Interactionsupporting
confidence: 93%
See 2 more Smart Citations
“…The significant genotype × location interaction implied that the responses of the genotypes changed depending on the environmental conditions. These finding are in agreement with the results reported by Balalić and Zorić (2013). There was no significant genotype × year interaction that means genotype behavior in a location between years is not significant.…”
Section: Analysis Of Variance and Nature Of Ge Interactionsupporting
confidence: 93%
“…The studied genotypes showed cross over types of GE interaction while environments showed both cross over and non-cross over types of GE interaction (Table 3). The relative contributions of G and GE interaction effects to the total variation for grain yield found in this study are in agreement with those found in other crop adaptation studies such as cereals or food legumes in rain-fed environments (Alagarswamy and Chandra, 1998;Balalić et al, 2011;Ceccarelli and Grando, 1991;Mohammadi et al, 2007;Sabaghnia et al, 2008;Živanović et al, 2012). Therefore, it would be very difficult to achieve an indirect response to selection over all of the canola target population of environments from selection in a few environments, ignoring the observed GE interactions. )…”
Section: Analysis Of Variance and Nature Of Ge Interactionsupporting
confidence: 92%
See 1 more Smart Citation
“…Highly significant negative correlations were found between grain yield and stability indices S i (3) and S i (6) in both progeny groups, and very strong and highly significant correlations were found between S i (3) and S i (6) values (Table 5). High values of rank correlation coefficients between S i (1) and S i (2) values were also found by DELIĆ et al (2009), FLORES et al (1998), SCAPIM et al (2000) and BALALIĆ et al, (2011). The presence of high rank correlations between stability indices S i (1) and S i (2) justifies the selection of one of them for the proper stability assessment.…”
Section: Correlations Between Yield and Non-parametric Stability Meassupporting
confidence: 58%
“…Also, Khalili & Aboughadareh (2016) have proposed some procedures to test the GxE interaction apart from methods based on analysis of variance. Among these nonparametric procedures, stable performance of genotypes evaluated under in MET were determined by Huehns' statistics (Balalić et al, 2011;Lima et al, 2013;Farshadfar et al, 2014). The objectives of this study were to apply nonparametric measures to estimate GxE interaction in coordinated trials to identify stable dual purpose barley genotypes possess high forage and grain yield.…”
Section: Introductionmentioning
confidence: 99%